THE AUTHENTICITY OF THE PHANTOM. ON NEW SIMULATION METHODS OF THE ALTERNATIVE PAST IN SCREEN CULTURE (based on the series Chernobyl) /ДОСТОВЕРНОСТЬ ФАНТОМА. О НОВЫХ МЕТОДАХ МОДЕЛИРОВАНИЯ АЛЬТЕРНАТИВНОГО ПРОШЛОГО В ЭКРАННОЙ КУЛЬТУРЕ (на примере сериала «Чернобыль») - POZHAROV ALEKSEY I. / ПОЖАРОВ А.И. (Наука телевидения, 2020)
The article analyzes the phenomenon of increased interest among the modern mass recipients in cultural artifacts that simulate various models of the phantom past, and in new ways of constructing it. Falsification of history for various purposes has been existing for a long time, but lately, the ways of presenting inaccurate versions of historical events have found a particularly sharp response from the audience. Beginning as conspiratorial literary and journalistic experiments to “rip off the veils”, phantom story models are now most successfully overspread in the form of amateur video content. Modern large-scale filmmaking, following the trend, also increasingly claims the authenticity of the depicted historical periods and events. An example of such approach is the careful study of the nuances of the texture that surrounded the Soviet people in the mid-80s in the series Chernobyl (directed by Johan Renck, USA, UK, 2019), which received a great response in the media space. The slogan of the film is “What is the cost of lies?” and its main message is the claim to the need of revealing the truth to the mass audience. As techniques aimed at creation of the authenticity illusion the series primarily uses the accuracy of details, costumes, make-up, decorations, which scrupulously reconstruct Soviet life in the eighties. The global plot and many subplots also generally correspond to the facts that happened in reality. Another technique of the series being traditional for the mockumentary genre which increases the recipient’s trust in the media product is the shaky camera. Imitation of amateur filming allows achieving a greater effect of involvement of the modern mass audience. Such techniques inspire confidence in the media product, reducing the criticality of its perception as a whole. However, after a detailed examination of the plot moves, it turns out that some of the events reflected in the series are presented perversely and one-sided, while others are in stark contrast to those that actually took place. In addition, the use of other artistic techniques such as, for example, specific color correction, stable cinematic clichés for the heroes’ characteristics, up to the frame structure, allow us to talk about imparting a biased meaning to the events. Thus, responding to the request of the mass audience, the authors create artifacts in which the accuracy in displaying fine details creates a feeling of authenticity, and the biased interpretation of the narrative, which uses specific artistic techniques, makes it possible to broadcast stories that are far from the historical truth. Such approaches make it possible to talk about the formation of new ways of constructing alternative historical models that inspire confidence in the mass audience. Статья посвящена анализу феномена повышенного интереса современного массового реципиента к культурным артефактам, моделирующим различные модели фантомного прошлого, и к новым способам его конструирования. Фальсификации истории в различных целях существовали долгое время, но в последнее время способы подачи недостоверных версий исторических событий находят особенно острый отклик у зрительской аудитории. Начавшись как конспирологические литературно-публицистические эксперименты по «срыванию покровов», в настоящее время модели фантомной истории успешнее всего распространяются в формате видеоконтента, создаваемого любителями. Современное крупное кинопроизводство, следуя за трендом, также все больше претендует на достоверность изображаемых исторических эпох и происходящих событий. Примером этого может служить тщательная проработка нюансов фактуры, окружавшей советского человека в середине 80-х годов, в сериале «Чернобыль» (реж. Йохан Ренк, США, Великобритания, 2019), получившего большой резонанс в медийном пространстве. Слоганом фильма является «Узнай цену лжи» и основным его посылом является претензия на необходимость открывать правду массовой аудитории. В качестве приемов, работающих на создание иллюзии достоверности, в сериале в первую очередь используется скрупулезная точность деталей, костюмов, грима, декораций, действительно точно воссоздающих советский быт восьмидесятых. Глобальный сюжет и множество побочных сюжетных линий также в целом соответствуют фактам, происходившим в действительности. Еще одним из приемов, традиционных для жанра мокьюментари и повышающих доверие реципиента к медиапродукту, использованным в сериале, является shaky camera. Имитация любительской съёмки позволяет достигать большего эффекта вовлечения у современного массового зрителя. Такие приемы вызывают доверие к медийному продукту, снижая критичность восприятия его в целом. Однако после подробного рассмотрения сюжетных ходов выясняется, что одни отраженные в сериале события подаются искаженно и однобоко, а другие — сильно расходятся с действительно имевшими место. Кроме того, использование других художественных приемов, таких как, например, специфическая цветокоррекция, устойчивых кинематографических штампов для характеристик героев, — вплоть до построения кадров, — позволяют говорить о придании происходящим событиям тенденциозной окраски. Таким образом, отвечая на запрос массового зрителя, авторы создают артефакты, в которых точность в отображении мелких деталей создает ощущение достоверности, а пристрастное освещение повествования с помощью специфических художественных приемов позволяет транслировать сюжеты, далёкие от исторической правды. Подобные подходы дают возможность говорить о формировании новых способов конструирования альтернативных исторических моделей, вызывающих доверие у массового зрителя.